Software defined radio platform with wideband tunable front end - Iancu, Daniel; Glossner, John; Nacer, Gary; Stanley, Stuart; Kolashnikov, Vitaly; Hoane, Joe (International Journal of Engineering and Technology, 2015)
The paper presents a Software Defined Radio (SDR) development platform with wideband tunable RF (Radio Frequency) front end. The platform is based on the SB3500 Multicore Multithreaded Vector Processor and it is intended to be used for a wide variety of communication protocols as: Time Division Duplexing/Frequency Division Duplexing Long Term Evolution (TDD/FDD LTE), Global Positioning System (GPS), Global System for Mobile/General Packet Radio Service (GSM/GPRS), Wireless Local Area Network (WLAN), Legacy Worldwide Interoperability for Microwave Access (WiMAX). As an example, we describe briefly the implementation of the LTE TDD/FDD communication protocol. As far as we know, this is the only LTE category 1 communication protocol entirely developed and executed in software (SW), without any hardware (HW) accelerators.